Nanotubos de TiO2 incorporados com prata e zinco sobre substratos de titânio: uma revisão sistemática e uma análise eletroquímica - Mendes, Douglas Thainan Silva Lima (2022)
Premature implant failures related to biofilm formation and implant corrosion are a worldwide health problem. Because of these issues, TiO2 coatings obtained by anodization can increase the corrosion resistance of the commercially pure titanium (CPTi) and the rate of Ca-P mineralization, unlike the naturally formed TiO2 layer, which is irregular and thin. Added to this, several bacterial strains, associated with biofilm formation, are resistant to antibiotics, reducing the effectiveness of this treatment. Thus, the inclusion of metals in TiO2, such as Zn, may be able to promote bactericidal action, being a substitute for antibiotic therapies. However, its effectiveness against infections is still contradictory. Therefore, the objectives of this work were: (i) to carry out a systematic review of the literature to answer whether, “Does the incorporation of Zn in TiO2 coating on titanium implants inhibit bacterial growth in vitro?”; (ii) to produce hybrid nanostructured TiO2 coatings, by anodization, individually incorporated with Zn (Zn.NTT) and Ag (Ag.NTT) nanoparticles to evaluate their capacity concerning corrosion resistance, bioactivity and bactericidal activity against CP-Ti. The systematic review showed, through meta-analyses, that there is a high degree of certainty that Zn provides the bactericidal effect. However, the coatings produced by anodizing to form TiO2 nanotubes and incorporated with NP of ZnO, using hydrothermal synthesis, provided homogeneity of statistical results, compared to other synthesis methods. The experimental results showed that the samples NTT, Ag.NTT and Zn.NTT presented higher surface energy concerning CP-Ti. Besides, CP-Ti did not promote the formation of Ca-P, while the EDS analysis suggests that there was the formation of Ca-P in the coatings. In the electrochemical tests, it was possible to estimate that Zn.NTT and Ag.NTT presented a more resistive behavior, in SBF, in comparison with NTT and CP-Ti, indicating that the presence of Zn and Ag on TiO2 potentiate the barrier effect against the corrosion. Furthermore, the hybrid coatings had more than one time constant that helps to maintain TiO2, making the coating even more resistive. Finally, the results of the antibacterial assays showed the formation of halos for Ag.NTT and Zn.NTT against S. aureus, indicating the antimicrobial potential of these coatings.